Funkcje polityczne parlamentu w Republice Austriackiej: [The political functions of the parliament in the Austrian Republic] (Studia Prawnicze / The Legal Studies, 2023)
The republican Austrian parliamentarianism has been in a state of permanent crisis since the day it was brought to existence by the Constitution of 1920. Generally speaking, this was due to the fact that the model of liberal parliamentarianism, set up by the constitution, has never corresponded to the requirements and aspirations of the political parties which in 1919 and 1945 stood behind all endeavours after reviving the Austrian state.In the last thirty years the period between 1945—664 witnessed the decline of the functions of the National Council (Nationalrat), whereas in 1966—76 the situation improved to the benefit of the latter. Nevertheless due mention should be made that the revival of the parliamentarianism, after a transfer had been made in Austria into one-party system, brought about the emergence of a new model of parliamentarianism, where authority rested with the government, the party and pressure groups. Consequently the parliament could not remain insensitive to this transformation. The latter resulted in present political functions and the form of constitutional functions, which were the outcome of the changing political situation in the country. Thus the division into three bodies of authority was retained (this, however, did not protect against the overgrowth of the latter), and the reform of the parliament was carried out. When its position in the political system was being established, there was oscilating between „modernizing” on the one hand and limitation of its constitutional powers on the other. The modernizing stood for a new role that the Council was endowed with — i.e. to articulate the interests of the party and pressure groups rather than the nation. With the assistance of the former two the Ausrian parliament became one of the most significant stabilizers of the existing system of political forces. It has transformed from a resolving and supervising organ into an institution which, within a determined political framework, is to safeguard the inviolability of the capitalist system. Thus determined positionnof the Council has already, become permanent within the political system and no changes should be expected in this respect. This is guaranteed by constantly increasing tasks of the state relating to socio-economic issues, as well as by the class-interests of the ruling forces.